An Exploration of Nurses' health beliefs: Ways of Knowing and Implications for Learning and Teaching - Teresa Stone; Jane Conway (Halla Newcastle Education and Research Center, 2018)
Background The origin, evolution and potential impact of personal ways of knowing, underpinned by health beliefs, are shaped by experience and sociocultural factors. These need to be explored if contemporary nurse educators and clinicians are to realize the goals of promoting healthy, positive outcomes for their clientele that are founded in other ways of knowing. Problem- based learning is argued to be an approach to the design of learning that encourages critical thinking and supports learners to develop new ways of thinking about real life problems. This requires an ability to integrate multiple ways of knowing to create and modify personal beliefs and learn. Method Q-methodology was used to gain the perspectives of nurses' health beliefs and sources of knowledge from 236 nurses, clinical and academic, from Thailand, South Korea, Australia, China and Japan. Results and conclusions The study revealed tensions between personal beliefs, often nested in cultural traditions, and contemporary evidence that counters those beliefs. Three themes relevant to nurses' 'ways of knowing' emerged: sources of belief, unexamined beliefs, and knowing from experience. The sorting process acted as intervention in itself to create dissonance within the nurses about the sources and veracity of their beliefs. The study illuminated a need to recognise that critical health literacy, seen as the hallmark of contemporary practice, may be at odds with personal beliefs, values and culture.